The effect of colchicine treatment on phenotype and genotype characteristics of Detam-2 variety of soybean Glycine max - F. FATHURRAHMAN; SARIPAH ULPAH; NOER AFNY MULIYATI SODIQ; IMAM MAHADI (Society for Indonesian Biodiversity, 2024)
Abstract. Fathurrahman F, Ulpah S, Sodiq NAM, Mahadi I, 2024. The effect of Colchicine treatment on phenotype and genotype characteristics of Detam-2 variety of soybean Glycine max. Biodiversitas 25: 1230-1238. The enhancement of soybean plant mutagenesis to obtain phenotypic and genotypic diversity is essential in agriculture. This study aimed to analyze the effect of colchicine concentration on phenotypic and genotypic characteristics based on RAPD markers of detam-2 variety. The experiments were carried out from January to June 2023 in the experimental farm of the Agriculture Faculty, Universitas Islam Riau, Pekanbaru, Indonesia. Therefore, 600 plants were used, consisting of 200 controls and 400 samples treated with 3,500 ppm of colchicine. The growth parameter was analyzed using a DMRT statistical test at p<0.05, and stomata densities were compared using T-test. The mutant-1 produced the highest yield, a total of 235 pods (with 233 phity pods), seed weighed 93.20 g, which was significantly different from those of controls. Mutant-2 produced the highest dry weight of 100 seeds, which was 12.80 g, with a dry seed weight per plant of 63.30 g. Leaf types in mutant samples varied, including normal, purple leaf stems, and curly leaves. The genotypic study showed that primer OPAA-01 produced a different number of DNA bands. The highest genetic similarity was 0.961 among the controls, while the lowest was 0.451 between mutant-1 and the controls. Based on the results, the dendrogram produced two groups: control and mutant-1.